Bistable non-volatile resistive memory devices based on ZnO nanoparticles embedded in polyvinylpyrrolidone. Issue 25 (13th April 2020) - Zhang, Hongyan; Zhao, Xiaofeng; Huang, Jiahe; Bai, Ju; Hou, Yanjun; Wang, Cheng; Wang, Shuhong; Bai, Xuduo
Abstract : The resistive random access memory (RRAM) devices based on polyvinylpyrrolidone (PVP) and PVP:PVP:zinc oxide nanoparticle (ZnO NP) active layers have bistable electrical switching behavior. Abstract : The resistive random access memory (RRAM) devices based on polyvinylpyrrolidone (PVP) and PVP:PVP:zinc oxide nanoparticle (ZnO NP) active layers have bistable electrical switching behavior. Herein, via a series of storage performance tests, it was proved that the ITO/PVP:ZnO/Al device has a higher ON/OFF current ratio and better memory performance than the ITO/PVP/Al device. Moreover, at 13 wt% concentration of ZnO NPs, optimal storage performance was obtained, the switch state current ratio significantly increased, and the threshold voltage obviously decreased. The conduction mechanism of the devices was further discussed. The device having inorganic nanoparticles embedded in the polymer has excellent storage performance, which has potential application value in data storage.